Utilization of E-wallet as Perceived by ABM Students of Bestlink College of the Philippines: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This study aimed to determine the utilization of e-wallets as perceived by ABM students atBestlink College of the Philippines during the 2022-2023 academic year.The result of this study revealed that the majority of respondents were young females whopreferred Gcash. The respondents had a positive utilization of e-wallets, with some concernsabout security and privacy policies.The study recommended that e-wallet providers offer training sessions and educationalmaterials, improve user experience and security measures, establish partnerships with localmerchants, and gather feedback. The proposed outputs included developing trainingmodules, improving user experience, implementing additional security measures, partneringwith local merchants, and establishing feedback mechanisms.
Keywords: Business